ANALYSIS OF OPINIONATED TEXTS ON IPL 2020 MATCHES USING SOCIAL MEDIA DATA - Dr. Sakthi Kumaresh , Muskaan Shah , Samyuktha Sathyanarayan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In India, The Indian Premier League (IPL) is a prominentand prestigious 20 overs cricket game conceptualizedwhere interstate teamswith a small representation of players from across countriescompete against each other to win the coveted trophy. Many leading icons from industry, films and sports enthusiasts own these teams with huge financial investment. Over the years IPL has become the largest revenue generating sports event in India. It has also brought about a sense of identity and belonging towards teamsas teams are named after cities where Indians reside. Usually,the matches are played in India at different locations. But, in 2020, because of Covid-19, the match venues were shifted to UAE and played without any audience. Given this context, public opinion about matches, cricketers and performance of teams are not only given out using live commentary but are usually expressed in the form of comments, tweets and opinion on several social media platforms. In this paper, Twitter posts (tweets) that relates to IPL teams and feedback of matches have been studiedand classifiedas positive and negative sentiments for understanding the sentiment and views of people about the different teams. Opinion mining has also been used to infer if people are happy watching the match at home or if they indeed want to go to the stadium to watch the match.